Effects of UV-ozone irradiation on copper doped nickel acetate and its applicability to perovskite solar cells. Issue 17 (18th April 2016) - Kim, Jeongmo; Lee, Hee Ryung; Kim, Hyeong Pil; Lin, Tengda; Kanwat, Anil; Mohd Yusoff, Abd. Rashid bin; Jang, Jin
Abstract : The effects of UV-ozone (UVO) irradiation on copper-doped nickel acetate and its applicability to perovskite solar cells were investigated. Abstract : The effects of UV-ozone (UVO) irradiation on copper-doped nickel acetate and its applicability to perovskite solar cells were investigated. UVO irradiation of copper-doped nickel acetate significantly increased the electrical conductivity (from 4.28 × 10 −4 S cm −1 to 5.66 × 10 −2 S cm −1 ), which is due to the increased carrier concentration (from 3.53 × 10 13 cm −3 to 2.41 × 10 16 cm −3 ), and the charge extraction efficiency was enhanced, leading to better compatibility with the hole transport layer. By UVO irradiation, the work function was increased from 4.95 eV to 5.33 eV by the surface dipole formation, which effectively reduced the interface barrier between the hole transport layer and the MAPbI3 light absorbing layer. UVO Irradiation of the underlying layer also allows the MAPbI3 precursors to form better morphology with highly arranged crystallinity. Compared to the cells using non-irradiated copper doped nickel acetate, UVO-irradiated copper-doped nickel acetate devices showed an enhanced open-circuit voltage (3% increase), short circuit current (16% increase), fill factor (5% increase), showing an enhanced power conversion efficiency of 12.2% (21% increase).